Djibouti : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) for Djibouti. Djibouti's National Initiative for Social Development ('Initiative Nationale pour le Developpement Social'-INDS) provides a comprehensive vision for economic growth and poverty reduction. Notwithstanding some important achievements of the PRSP-I, overall progress in achieving its objectives has been limited. IMF staff commends the government for a well-designed and ambitious poverty reduction strategy. IMF staff considers that the INDS benefits from better prioritization and draws lessons from the shortcomings in the implementation of the PRSP-I.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet